Perbedaan Individual Mahasiswa dalam Mata Kuliah Pengantar Akuntansi 1 dan Implikasinya dalam Pembelajaran - Elvi Rahmi (Universitas Negeri Padang, 2018)
The objective of this study is to descript the individual students differences in the Introduction to Accounting 1 course and how is the implications in learning process. This study uses a quantitative descriptive approach. The population is all of students of the Department of Economics, who took Accounting Introduction 1 course, during The period from July to December 2018, and the sample are 32 students. Data were analyzed using descriptive analysis. Research results showed that students had different educational backgrounds who came from Senior High School majoring in Science, Senior High School majoring in Social Sciences, Vocational High School majoring in Accounting and Vocational High School not majoring in Accounting, From research data, it is also known that there are differences in the ability of students to take part in Accounting learning and only 33.33 % of students who are interested will choose accounting as their choice of expertise. From the results of the study it was suggested to the lecturers who supervise the Accounting Introduction 1 to use multi instructional methods so that individual student differences can be minimized.